Establishment and operation of a museum in Namangan - Karimov , Islomjon (The Lingua Spectrum, 2025)
This article provides information about the organization of the State Museum of history and culture of the Namangan region, the individuals who initiated the creation of the museum, the material and technical base and activities of the museum in the 20-30s of the 20th century.